THE ROLE OF SOCIAL CAPITAL IN IMPROVING INNOVATIVE BEHAVIOUR AND HUMAN RESOURCES PERFORMANCE IN SEMARANG REGENCY GOVERNMENT - Ema Puspitosari; Heru Sulistyo (UNISSULA, 2017)
The purpose of this study was to test a model in which social capital and information technology predict innovative behaviour and human resource performance. A total of 105 respondents completed questionnaires on social capital, information technology, innovative behaviour, and human resource performance. Results from structural equation modeling based smartPLS 3.0 confirmed that 1) social capital was positively related to innovative behaviour and human resource performance; 2) innovative behaviour was positively related to human resource performance; and 3) information technology moderated the relationships between innovative behaviour and human resource performance.Keywords: Social capital, Innovative. behaviour, Information technology, Human resource performance.